A case of severe subcutaneous emphysema in the post-operative period following cleft lip surgery - Vijayakumar, B (Medknow Publications, 2010)
Subcutaneous emphysema is not an unknown complication following cleft lip surgery. We describe a case of severe subcutaneous emphysema that developed six hours after surgery. The laryngoscopic intubation was smooth. Following subcutaneous emphysema the patient was treated conservatively with mask oxygen and spontaneous resolution occurred within 48 hours.